Prune belly syndrome – Case report and review of the literature - Leung, Alexander KC; Yu, Ho Kun Adrian; Hon, Kam Lun (Indian Journal of Child Health, 2014)
We describe a 2-year-old boy seen in Kenya who presented with fever, dysuria, foul smelling urine, and diarrhea. His previous ultrasonography showed an overdistended bladder and hydronephrosis. Physical examination revealed a distended abdomen, loose abdominal wall muscles with thin, flabby, and wrinkled skin on the abdominal wall, hypoplastic scrotum, and bilateral cryptorchidism. A diagnosis of prune belly syndrome was promptly made. The urinary tract infection was duly treated with intravenous ceftriaxone and the child followed by pediatric urology.